2017
DOI: 10.7554/elife.25158
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 regulates Ras-related protein R-Ras2 by lysine defatty-acylation

Abstract: The Ras family of GTPases are important in cell signaling and frequently mutated in human tumors. Understanding their regulation is thus important for studying biology and human diseases. Here, we report that a novel posttranslational mechanism, reversible lysine fatty acylation, regulates R-Ras2, a member of the Ras family. SIRT6, a sirtuin with established tumor suppressor function, regulates the lysine fatty acylation of R-Ras2. In mouse embryonic fibroblasts (MEFs), Sirt6 knockout (KO) increased R-Ras2 lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 40 publications
7
80
1
Order By: Relevance
“…After optimizing the NEM capping, biotinylation, Neutravidin enrichment and NH 2 OH elution conditions (SI Figure 12-14), we found that inclusion of Rapigest, a MS-compatible detergent was essential for efficient thioester hydrolysis, solubility and final elution of transmembrane proteins (CANX and IFITM3) from the beads (Si figure S14A). However, elution of RAS from beads was not complete, suggesting that alk-16 could have been metabolized or incorporated to another residue than Cys, consistent with recent report of Nε-Lys fatty-acylation of Ras isoforms 42 . VCP was used as a control to confirm that the elution was thiol-specific (Figure 3).…”
Section: Resultssupporting
confidence: 88%
“…After optimizing the NEM capping, biotinylation, Neutravidin enrichment and NH 2 OH elution conditions (SI Figure 12-14), we found that inclusion of Rapigest, a MS-compatible detergent was essential for efficient thioester hydrolysis, solubility and final elution of transmembrane proteins (CANX and IFITM3) from the beads (Si figure S14A). However, elution of RAS from beads was not complete, suggesting that alk-16 could have been metabolized or incorporated to another residue than Cys, consistent with recent report of Nε-Lys fatty-acylation of Ras isoforms 42 . VCP was used as a control to confirm that the elution was thiol-specific (Figure 3).…”
Section: Resultssupporting
confidence: 88%
“…The two models are not mutually exclusive, or contradictory, since it is possible that HDAC11's deacetylase activity could be increased upon chromatin binding which allows for deacetylation of histones, while it functions efficiently as defatty-acylase in the cytosol. A similar mechanistic function has been reported for SIRT6, a member of the NAD + -dependent HDAC 31,32 .…”
Section: Discussionsupporting
confidence: 76%
“…Our study presented here indicate that SHMT2 is regulated by lysine fatty acylation, which has only been known to occur on a few proteins in mammalian cells. [28][29][30][31] Our data suggest that lysine fatty acylation does not alter the enzymatic activity of SHMT2, but instead promotes the recruitment of the BRISC complex to IFNR1 ( Figure 5F). .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Structural studies of MT-bound MAPs typically reveal conformational changes in the MAP on interaction with the MT lattice. In the most extreme cases, unstructured proteins such as members of the tau/MAP2 family and the mitotic regulatory protein TPX2, become at least partially ordered when in contact with MTs 36,37 . A recent study of the plant MAP Companion of Cellulose synthase 1 also showed similar behaviour in its disordered N-terminus on binding MTs 38 .…”
Section: Discussionmentioning
confidence: 99%